Larval morphology of three syntopic species of Kaloula Gray (Anura: Microhylidae) from Vietnam - Vassilieva, Anna B. (Zootaxa, 2021)
The external larval morphology of three species of the microhylid genus Kaloula (K. indochinensis, K. mediolineata, and K. pulchra) inhabiting the southern and central regions of Vietnam is studied. The similarities and the distinctive features of their morphometric characters, the structure of their mouthparts and spiracle, and their coloration are analysed with consideration of the geographic variability. A description of the tadpole of K. indochinensis is provided for the first time. The interspecific comparison revealed the shape of the mouthparts and the spiracle as the most reliable diagnostic characters for the field identification of the coexistent Kaloula tadpoles. The first description of the larval chondrocranium and hyobranchial apparatus of K. indochinensis demonstrates a set of morphological traits characteristic of suspension-feeding microhylids. Some developmental parameters (egg number and size, duration of embryonic and larval development, larvae size and stage at hatching) are provided for K. indochinensis and K. pulchra.